The Impact of Product, People, Process Dan Physical Evidence on Customer Loyalty at PT. Samudera Shipping Services - Surabaya - * Mukhsinah (JMM17 : Jurnal Ilmu ekonomi dan manajemen, 2014)
This study aims to determine the effect of product, people, process and physical evidence on customer loyalty St PT. Samudera Shipping Services - Surabaya. The variables used in this study are the independent variable ( X ) consisting of the Product ( X1 ) , People ( X2 ) , Process ( X3 ) , and Physical Evidence and the dependent variable ( Y ) that is customer loyalty. The theory used is Kotler & Keller ( 2009 ) marketing mix refers to the concept of the traditional marketing mix consists of 4Ps , namely product , price , place / location and promotion expanded with the addition of non- traditional elements , namely people , physical facilities and processes to be seven elements (7P) . However, the study was taken 4 P, which are product, people, process and physical evidence. And the Sheth theory on Tjiptono (2012:482) customer loyalty is a deeply held commitment to re- buy or subscribe to a product / service consistently preferred in the future, giving rise to a series of purchase of the product or the same product over and over, despite situational influences and marketing efforts have the potential to cause switching behavior to similar competitors. This study of causal research is looking for a research and describe the relationship (cause and effect) and the effect of study variables to be concluded (Maholtra , 2005 , p.100 ) . The population that will be used and examined in this study are customers of PT. Samudera Shipping Services Branch Office Surabaya in 2011-2013. Data analysis techniques used in this research is to use the method of Structural Equation Modeling (SEM) with software Smart PLS (Partial Least Square). The study results showed that the product variable significant positive effect on loyalty , the value of t - statistic greater than 1.96 indicates that 3,020 . These results indicate that the first hypothesis , H1 : Product effect on loyalty , is accepted . For people variable has no effect on customer loyalty , the value of t - statistics that show less than 1.96 which is 1,163 . So the second hypothesis ( H2 ) "The effect on customer loyalty " , be rejected . Process Variables significant positive effect on customer loyalty , the value of t - statistic greater than 1.96 indicates that 2,420 . These results indicate that the third hypothesis ( H3 ) " Process effect on customer loyalty " stated diterima.Variabel physical evidence significant positive effect on customer loyalty , the value of t - statistic greater than 1.96 indicates that 5,335. These results indicate that the fourth hypothesis ( H4 ) " Physical evidence effect on customer loyalty " , is accepted.Keyword : product, people, process ,physical evidence, customer loyalty